The Influence of Modernization of Tax Administration System and Trust in Government on Taxpayer Compliance with Taxpayer Morale as a Moderating Variable - Fabian, Danu; Herianti, Eva (Pertapsi-Indonesia collaborated with Petra Christian University, 2025)
This study examines the impact of tax administration system modernization and trust in government on taxpayer compliance, with taxpayer morale as a moderating variable. Primary data was collected through questionnaires distributed to MSME taxpayers at Block A, Tanah Abang Market, Central Jakarta. Using a quantitative approach, the research applied purposive sampling with the Slovin formula and analyzed data via SEM Partial Least Square using SmartPLS 4. Findings reveal that tax administration modernization and trust in government significantly and positively influence taxpayer compliance. However, taxpayer morale weakens the effect of tax administration modernization on compliance and does not moderate the impact of trust in government. Limitations include time constraints, varied respondent characteristics, and potential biases in questionnaire responses. This research contributes to tax authorities by emphasizing the need for efficient systems and trust-building policies to enhance compliance. It addresses a gap by introducing taxpayer morale as a moderating factor.